Reform in the dental services area in Romania – objective necessity or second option - UŢĂ, Cristian (Annals of Spiru Haret University. Economic Series, 2011)
The article herein deals with a topic of current interest, not only because the latest economic and social phenomena within the context of globalized crisis in the world, but also from the perspective of the evolution and specific processes in the medical area in Romania. The writer accomplishes a journey into the various medical systems in national economies, by analyzing the features of each type of system and the opportunity for a ‘capitalist’ vision related to the healthcare services in general. The dental medical services share a series of characteristics that help them be better defined from the point of view of provider-customer relation. Thus, it becomes evident that, for Romania, the process initiated in 2006 meaning liberalization of practicing the dental doctor profession represents a natural way of developing the market specific to such services. From this perspective, this issue targets the mentalities level only – to impose quality standards on the market and to witness the offer-demand balance, both deriving from the specific nature itself of the dental services. The involvement of the authorities at Health Department into developing a health insurance policy in the dental field and the support of the private initiative in the underserved areas are the main targets of the ‘reform’.